2015
DOI: 10.1017/s0022215115001127
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of otitis media in children and assessment of treatment options

Abstract: The success rate in patients treated with antibiotics makes this option mandatory for an established diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…From these, 32 articles were also excluded as the outcome of interest was missing, insufficient and/or ambiguous, and 2 articles were not accessible in full text [22,23]. Fifty-two studies were evaluated by a full-text review and 16 studies had data collection period before 2009 and three studies [24][25][26] have no record of the data collection period. Finally, 33 articles passed the eligibility criteria and quality assessment and hence included in the study (Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…From these, 32 articles were also excluded as the outcome of interest was missing, insufficient and/or ambiguous, and 2 articles were not accessible in full text [22,23]. Fifty-two studies were evaluated by a full-text review and 16 studies had data collection period before 2009 and three studies [24][25][26] have no record of the data collection period. Finally, 33 articles passed the eligibility criteria and quality assessment and hence included in the study (Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Children aged less than six months are considered high risk because recurring bouts of otitis media may predispose them to complications that include speech difficulties and hearing loss. 1,2 In our study, we reported the highest incidences of non-resolving acute otitis media following initial paracetamol usage in children aged 7-12 months (43.5 per cent) and 2-5 years (42.1 per cent). 3 In chronic suppurative otitis media (CSOM) where microbial aetiology is implicated, it is important that antibiotics be given.…”
Section: Authors' Replymentioning
confidence: 52%
“…Dear Editors, I came across a very interesting article published in your esteemed journal titled 'Occurrence of otitis media in children and assessment of treatment options' by Nwokoye et al 1 The study had been well planned and was very thought provoking. However, I beg to differ from the author's conclusion and would like to highlight the same through your esteemed journal.…”
mentioning
confidence: 99%
“…Recurrent AOM can develop into chronic otitis media, which often requires surgical intervention such as myringotomy and placement of tympanostomy tubes for ventilation and drainage [7][8][9]. Chronic otitis media has also been associated with sensorineural hearing loss, which may lead to speech and learning deficits [9][10][11][12][13]. In the US alone, 500,000 children undergo tympanostomy surgery annually at a cost of $5 billion [14].…”
Section: Incidence and Severity Of Acute Otitis Mediamentioning
confidence: 99%